Aspek positif di kampus merdeka: perspektif mahasiswa keguruan - Hasanah, Enung; Al Ghazi, M. Ikhsan; Badar, M. Ikhwan Al (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This study aims to identify the positive experiences of education students related to learning in the Kampus Merdeka program. The research employs a qualitative method, involving 12 participants who are students from the teacher education program. Data were collected through in-depth interviews and analyzed using thematic analysis techniques. The findings reveal three main themes identified by the students as positive aspects of learning in the Kampus Merdeka program. First, the flexibility of the curriculum, which allows students to select courses based on their interests and career needs. Second, the innovative quality of instruction, encompassing the use of creative teaching methods and advanced educational technology. Third, the availability of career guidance, which assists students in preparing for their future careers. These findings indicate that the implementation of Kampus Merdeka has a significantly positive impact on the learning experiences of education students.